2018
DOI: 10.1111/pai.12922
|View full text |Cite
|
Sign up to set email alerts
|

Wheeze trajectories are modifiable through early‐life intervention and predict asthma in adolescence

Abstract: Using data-driven methodology, children can be classified into clinically meaningful wheeze trajectory groups that appear to be programmed by modifiable and non-modifiable factors, and are useful for predicting asthma risk. Early-life interventions can alter some wheeze trajectories (ie, Early-Persistent) in infancy and reduce wheezing prevalence in mid-childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
70
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(73 citation statements)
references
References 32 publications
(89 reference statements)
2
70
1
Order By: Relevance
“…Our findings reinforce the evidence for distinguishing early transient wheezing, that recovers spontaneously, from atopic persistent wheezing, as previously shown by Martinez et al and confirmed by more recent studies that also reported several persistent profiles . We observed one profile of persistent wheezers that might gather all non‐transient wheezers, as separation between these profiles is not so clear‐cut, and overlay between related clinical features—including atopic status and lung function—has been reported .…”
Section: Discussionsupporting
confidence: 91%
“…Our findings reinforce the evidence for distinguishing early transient wheezing, that recovers spontaneously, from atopic persistent wheezing, as previously shown by Martinez et al and confirmed by more recent studies that also reported several persistent profiles . We observed one profile of persistent wheezers that might gather all non‐transient wheezers, as separation between these profiles is not so clear‐cut, and overlay between related clinical features—including atopic status and lung function—has been reported .…”
Section: Discussionsupporting
confidence: 91%
“…Clearly, it is important to identify early risk factors for asthma, as well as wheeze trajectories, in order to apprehend the disease as shown recently in PAI. [10][11][12] Other recent studies have also shown that global, or allergen-specific sensitization (hen's egg) may change the prevalence of respiratory allergy at a later age. 13,14 Accidental allergic reactions in the community are a major concern to parents and health professionals.…”
Section: Fecal Metabolites and Early Sensitization Influence Asthma mentioning
confidence: 99%
“…Sensitization to multiple allergens at single time‐points, increasing sIgE levels and SPT wheal sizes, and persistent sensitization during childhood were associated with increased risk of asthma at age 13, suggesting the use of quantitative and repetitive sensitization measurements when assessing the risk of developing asthma. Clearly, it is important to identify early risk factors for asthma, as well as wheeze trajectories, in order to apprehend the disease as shown recently in PAI . Other recent studies have also shown that global, or allergen‐specific sensitization (hen's egg) may change the prevalence of respiratory allergy at a later age …”
mentioning
confidence: 99%
“…They also point out that this increase in lung function was not associated with any clinically relevant protective effect on allergy and asthma development. Asthma development in relation to the environment is a key issue in allergy and asthma prevention, which might largely influence the long‐term prognosis of asthma‐affected children 4,5 . PAI has recently reported other studies in relation to the topic.…”
mentioning
confidence: 99%